Analysis and application of in-situ stress in metal mining area of Chinese mainland - LI Peng; MIAO Sheng-jun (工程科学学报)
Based on the measured in-situ stress data of the metal mining area in China, 165 sets of data were finally adopted after optimized treatment, which basically covers the distribution area of the main metal mines in the Chinese mainland. The characteristics of in-situ stress field in the buried depth of the metal mining area in China were presented by regression analysis method, and the stability of the fault of the metal mining area in China was discussed from the ground stress. The results show that the vertical principal stress, the maximum horizontal principal stress and the minimum horizontal principal stress in the metal mining area of Chinese mainland generally increase linearly with the depth. The difference between maximum and minimum horizontal principal stresses (Δσ) increases with the depth, but the regularity is not significant. The ratio of maximum horizontal principal stress to vertical principal stress (Kh,max), the ratio of minimum horizontal principal stress to vertical principal stress (Kh,min) and the ratio of average horizontal stress to vertical principal stress (Kh,av) mainly concentrate in the interval of 1. 00 to 2. 50, 0. 50 to 1. 50, and 1. 00 to 2. 00, respectively. With the increase of depth, the variation amplitudes of the three lateral pressure coefficients decrease gradually:Kh,max, Kh,min and K h,av tend to 1. 83, 0. 80 and 1. 31, respectively. The ratio of maximum horizontal principal stress to minimum horizontal principal stress has no obvious regularity with the depth, and the values mainly concentrate from 1. 5 to 2. 0, approximate to normal distribution. Metal mining area has the possibility of fault slip when the depth is less than 500 m, and the reverse fault has the possibility of sliding while the strike slip fault is in a relatively stable state when the depth is more than 500 m.